2019
DOI: 10.1007/s13365-019-00740-3
|View full text |Cite
|
Sign up to set email alerts
|

Microglial cell depletion is fatal with low level picornavirus infection of the central nervous system

Abstract: Microglia are the only resident myeloid cell in the central nervous system (CNS) parenchyma, but the role of microglia in the context of neurotropic viral infection is poorly understood. Using different amounts of Theiler's murine encephalomyelitis virus (TMEV) in a preclinical model of epilepsy and PLX5622, a colony stimulating factor-1 receptor inhibitor that selectively depletes microglia in the CNS, we report that microglia-depleted, TMEV-infected mice develop seizures, manifest paralysis, and uniformly su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 14 publications
9
55
0
Order By: Relevance
“…The early inflammasome activation of microglia appears to be an important general mechanism of infection control in the CNS. There is agreement between studies, that microglia depletion by pharmacological inhibition of the CSF‐R1 exacerbates disease in diverse models of virus infection of the brain (Sanchez et al, ; Seitz, Clarke, & Tyler, ; Waltl et al, ; Wheeler & Quintana, ). This may be due to a role of microglia in the local restimulation of CD8 + T‐cells (Funk & Klein, ).…”
Section: Microglia and Macrophages In Inflammatory Diseases In Humansmentioning
confidence: 80%
“…The early inflammasome activation of microglia appears to be an important general mechanism of infection control in the CNS. There is agreement between studies, that microglia depletion by pharmacological inhibition of the CSF‐R1 exacerbates disease in diverse models of virus infection of the brain (Sanchez et al, ; Seitz, Clarke, & Tyler, ; Waltl et al, ; Wheeler & Quintana, ). This may be due to a role of microglia in the local restimulation of CD8 + T‐cells (Funk & Klein, ).…”
Section: Microglia and Macrophages In Inflammatory Diseases In Humansmentioning
confidence: 80%
“…6,43 Because mTOR is ubiquitously expressed in neurons and microglia, recent studies have specifically targeted mTOR hyperactivation in microglia 44 as well as CSF1R signaling. [45][46][47] A microglia-specific TSC1 KO mouse model produced an mTOR hyperactivation phenotype that resulted in an increase in the number of microglia with enhanced phagocytic activity in the hippocampus. 44 In these mice, the altered microglial properties correlated with reduced densities of excitatory and inhibitory synapses, and with the development of SRS.…”
Section: Microglial Proliferationmentioning
confidence: 99%
“…46 Similarly, treatment with the CSF1R inhibitor PLX3397 decreased both the number of IBA1-positive microglial cells in the hippocampus and seizure frequency in a mouse model of pilocarpine-induced SE. 45 Although these studies suggest that suppressing microgliosis during epileptogenesis is beneficial, recent studies also showed that total ablation is detrimental, 47,50 thereby suggesting that microglia have multiple roles. Ablation of microglia with the CSF1R inhibitor PLX5622 exacerbated the seizure phenotype and the mortality rate in epileptic mice induced with the Theiler murine encephalomyelitis virus.…”
Section: Microglial Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously determined that macrophage infiltration, more specifically IL-6-producing macrophages [15,22,35,36], but not T cell or neutrophil infiltration, is important for seizure development [22]. Recently, we and others have also demonstrated that macrophages and microglia have unique roles in controlling viral infection in the brain [37][38][39].…”
Section: Introductionmentioning
confidence: 99%